Regeneration the cultural axis Emphasizing the enhancement of the quality of the environment (case study : Enghelab Street,Intersection of Enghelab Square and Ferdowsi Square) - mina bakhshi; Saeed piri; Alireza Estalaji (تحقیقات کاربردی علوم جغرافیایی)
cultural axes as Part of public spaces in cities Play an important role in meeting human needs Many urban theorists Cultural Aspects As One of the main components of a city system is known Because along with its functional role Increase community in urban spaces so In order to further these spaces And to meet the needs of the people We must pay attention to the quality of perception of the environment And examined them in this research Such an approach is in re-creation By identifying and evaluating the dimensions and principles of recreation Promoting the quality of environmental perception in the Enghelab axis The aim of this study Recreation of the cultural axis of Enghelab Street Emphasizing the quality of environmental perception current study A field research with a descriptive-analytic approach And looking for the answer to this question,What are the socio-cultural components of social regeneration in relation to the components of the quality of environmental perception? To formulate a theoretical framework  First, using the documentary method The theoretical basis of the subject is detailed And then Analyzing existing approaches Emphasizing the quality of the environment Trying to rationalize the arguments As a result, a conceptual framework has been developed for this purpose In addition to the qualitative analysis of urban spaces In that quantitative analysis of the indicators has been done using a questionnaire To measure collected data Regression statistical test To measure the factors affecting regeneration And the quality of the environment,Pearson Correlation Test To measure the relationship between the components of perceptual quality and regeneration And Friedman test in order to prioritize each indicator And the average rating of the indicators Citizens' perspective is used The results Suggests that Among the indicators, Respectively,Environmental component, first priority and then content component Promote the quality of the environment